New records of phytoplankton from wetlands of Lalmai hill areas of Cumilla: Chlorophyceae (Bangladesh Journal of Botany, 2025)
Phytoplankton samples were collected from different wetlands of Lalmai Hill areas of Cumilla from October 2017 to September 2019. A total of 168 samples of phytoplankton were collected from which 352 species of Phytoplankton were identified where 40 species were found as new records for Bangladesh. The present paper includes 14 taxa of Chlorophyceae as new records for Bangladesh. These include eight species from Scenedesmus, two species from Tetrastrum and Crucigenia mucronata (G.M. Smith) Komárek, Euastrum denticulatum var. quqdriferium F. Gay ex Willi Krieger, Keratococcus suecicus Hind. and Pediastrum duplex var. asperum (A. Braun) Hansgirg.Bangladesh J. Bot. 54(1): 33-38, 2025 (March)